Model-Model Partisipasi Dalam Dunia Pendidikan Di Kota Samarinda - Abdi, Muhammad Iwan (LP2M IAIN Samarinda, 2012)
Participation is an active and initiative process that comes from citizen where it will be realized as an actual effort if fulfilling three factors; a good will, ability and a change to participate. In the context of education, the social participation is found in the form the people participation to the process of education. That participation and involvement can be in terms of management development aspect, curriculum, to the learning process. This paper tries to describe the models of social participation at SMP Plus Melati since this is one of the best schools in Samarinda. The models of social participation were found, such as: institutional, educative, and cultural participation. There are also some cooperation, such as: institutional mutual understanding, managerial development, finance, curriculum, and cooperation with some Moslem leaders in Samarinda.